Effect of Diverse Compost Products on Soilborne Diseases of Potato. Issue 3 (3rd July 2018) - Wilson, Carolyn; Zebarth, Bernie J.; Goyer, Claudia; Burton, David L.
ABSTRACT: Soilborne diseases result in major economic losses for potato producers. Compost application can reduce soilborne diseases, however the effects of compost products on potato disease severity and incidence are still unclear. Diverse compost products were compared for their effects on soilborne diseases of potato in New Brunswick, Canada using field and growth room experiments. In the field, five products were applied at 45 Mg ha −1 dry weight to field plots in October of 2014 and 2015. In the growth room experiment, seven products were mixed to a 5% w/w ratio with naturally infested soil. Tubers were assessed for disease severity and incidence and compared with a no compost addition control. Severity of symptoms of silver scurf, black scurf (BS), common scab (CS), and powdery scab varied among treatments, experiments, and years. In the field experiment, BS severity was significantly greater in the control than in the poultry manure compost treatment (3.26% versus 0.90%) in 2016. Common scab severity and incidence in the field were positively related to soil pH and negatively related to soil particulate organic matter C and compost C concentrations. In the growth room experiment, CS severity was significantly greater in the control (8.98%) than in the municipal source separated organic compost and sea-waste compost treatments (1.72 and 2.47%, respectively). In this study, compost products had a significant, but inconsistent, suppressive effect on soilborne potato diseases. The quantity of compost C, rather than compost quality, was likely the most important factor in disease suppression in this study.